Locations and dis-locations of personal, public and imaginary space in the visual production of ten women artists working in South Africa - Nolte, Jacqueline (Department of Historical Studies, 2024)
The dissertation centres on the location and dislocation ofpersonal, public and imaginary space in the work often women artists in South Africa. It does this toward understanding the relationship between the manifestation o f the artists' processes o f imagining and the shaping o f their identities. The term 'locations' is used to refer to areas, or sites, in which 'personal' and 'public' identity is enacted. Determinants oflocations are identified in relation to ancestry and the constructs of 'race', class, gender and sexual identity. These determinants are recognised as always multiple and mutually configuring. In addition to this, 'locations' are regarded in terms of how the artists have survived, engaged, and transformed their circumstances. The term 'dislocations' pertains to the effects ofoccupying designated sites and, more specifically, to disrupted positions within these sites. The dissertation investigates how the women have used their creativity to contradict disruption and suffering and how they have repositioned themselves through the art making process. Interviews were conducted and secondary sources and artworks studied in terms o f issues o f identity, power and agency. Understanding the locations ofthe women in relation to their agency as artists necessitated an acknowledgement o f their reflections on themselves. This research cannot, therefore, claim the status ofbeing complete or objective and, ofnecessity, it is participatory. Each artist is shown to be situated in determining locations ofplace and as practising within particular discourses, but always existing in relation to others and as a selfthat is becoming through the making of creative products. What is demonstrated is that the creative product participates in the realisation ofcontinuous identity formation by virtue ofthe operation ofmemory, which ensures the contact ofselfwith the abstract yet creative potential within space. Throughout this dissertation it is demonstrated that the artists experience memory as embodied experience and that the formation ofmemory is analogous to the art making process. The correlation between the artists' experience and their creative embodiment o f idea in matter ensures that their consciousness oflocation and selfis shared with others, thereby ensuring an evolution o f self in relation to others. Their encounter with potentiality enables these women artists to move beyond situations mired by the violence and violations of apartheid history.